Investigating the Capability of HEC-RAS Model for Tsunami Simulation - Rifa Amaliah; Bobby Minola Ginting (Journal of the Civil Engineering Forum, 2023)
This study highlights the simulation of tsunami cases using HEC-RAS 6.1. The primary aim is to evaluate the capability of the software in performing tsunami simulation due to its standalone computational framework (pre-processing, execution, and post-processing stages), making the modeling process interactive. The model accuracy was tested against some benchmark cases of wave propagation, including analytical solutions, laboratory experiments, and field measurements. The results showed HEC-RAS was capable of modeling tsunami propagation. The maximum elevation and velocity magnitude were accurately computed for the analytical cases. Furthermore, sufficiently accurate results were obtained for the laboratory case, where the maximum elevation was properly computed. For the field cases, the wave arrival time and the fluctuations of water surface and velocity were appropriately calculated. The Root Mean Square Error values between the numerical results and the analytical/observed data were relatively low below 30%, with the Pearson Product Moment Correlation values ranging from 52–99%. In addition to its eminence, a drawback was found regarding the graphical user interface (GUI) of HEC-RAS for the input of boundary conditions. These findings will be beneficial for the coastal engineering community and the continuous development of HEC-RAS.